Pelatihan Strategi Pengenalan Bahasa Inggris pada Siswa PAUD bagi Guru PAUD Wineha di Diwek Jombang - Laili, Elisa Nurul; Zuhriyah, Mukminatus; Fajarina, Maskhurin; Ma’rifatulloh, Sayid; Agustina, Ria Kamilah (Universitas Pahlawan Tuanku Tambusai, 2024)
Children, especially at the early childhood education level, are the nation's assets who will become future state leaders. Therefore, introducing English to elementary school children is crucial to enhance their abilities to pursue higher education. Learning and familiarizing themselves with English, as an international language of communication, can begin with reading, pronouncing, and forming simple sentences. An analysis of the situation at PAUD Wineha in Keras Village, Diwek Subdistrict, Jombang Regency, shows that PAUD teachers need